Konflik Batin Tokoh dalam Novel Alisya Karya Muhammad Makhdlori - Kamilia, Khosiatul (Jurnal Simki Pedagogia, 2021)
The problem in this research is the inner conflict experienced by Alisya, Sandy and Mamat/Ahmad. This can be seen from the inner conflict that occurs in the character of the Novel Alisya by Muhammad Makhdlori (the study of Literary Psychology) according to Sigmund Freud. The methot used is a qualitative descriptive methot, namely by describing the inner conflict that occurs in Alisya’s Novel character. Data collection is used by reading and taking notes. The source of this reseachis the Alisya novel by Muhammad Makhdloei with 301 pages publishes by Safirah, 2012 first printing. The reseach data is the inner confict that occurs in the character of the Alisya Novel by Muhammad Makhdlori (Study of Literary Psychology) according to Sigmund Freud. The results of this study are described as follow: there ia an inner conflict that occurs in the form of Id, Ego and Superego.